Antibacterial photodynamic activity of hydrophobic carbon quantum dots and polycaprolactone based nanocomposite processed via both electrospinning and solvent casting method - Ghosal, Kajal; Kováčová, Mária; Humpolíček, Petr; Vajďák, Jan; Bodík, Michal; Špitalský, Zdenko (Photodiagnosis and photodynamic therapy, 2021)
Inhabitation of various types of bacteria on different surfaces causes vital health problems worldwide. In this work, a wound dressing defeating bacterial infection had been fabricated. The antibacterial effect of polycaprolactone and hydrophobic carbon quantum dots (hCQDs) based nanocomposite has been presented. The nanocomposite was fabricated both via solvent casting and electrospinning method. Nanocomposites with and without hCQDs had been investigated. A detailed study on their morphology and surface properties were performed by scanning electron microscopy, atomic force microscopy and Raman spectroscopy. Prepared nanocomposites had been evaluated by the contact angle, UV-Vis spectroscopy, electron paramagnetic resonance spectroscopy, and antibacterial activity. It was found that nanocomposites were able to produce singlet oxygen upon blue light irradiation at 470 nm, and they were effective in the eradication of Gram positive (Staphylococcus aureus, Listeria monocytogenes) and Gram negative (Escherichia coli, Klebsiella pneumoniae) bacteria.
Keywords: Photosensitizing Agents; Nanocomposites; Photochemotherapy; fotosenzibilizující látky; Carbon; Quantum Dots; polyestery; uhlík; Anti-Bacterial Agents; Solvents; fotochemoterapie; antibakteriální látky; kvantové tečky; Polyesters; rozpouštědla; nanokompozity